Dao Companion to ZHU Xi’s Philosophy - Wu, Qichao; Huang, Yong (Dao Companions to Chinese Philosophy, 2020)
Zhu Xi (1130-1200) has been commonly and justifiably recognized as the most influential philosopher of Neo-Confucianism, a revival of classical Confucianism in face of the challenges coming from Daoism and, more importantly, Buddhism. His place in the Confucian tradition is often and also very plausibly compared to that of Thomas Aquinas, slightly later, in the Christian tradition. This book presents the most comprehensive and updated study of this great philosopher. It situates Zhu Xi’s philosophy in the historical context of not only Confucian philosophy but also Chinese philosophy as a whole. Topics covered within Zhu Xi’s thought are metaphysics, epistemology, ethics, political philosophy, hermeneutics, philosophy of religion, moral psychology, and moral education. This text shows both how Zhu Xi responded to earlier thinkers and how his thoughts resonate in contemporary philosophy, particularly in the analytic tradition. This companion will appeal to students, researchers and educators in the field.